FACÇÕES CRIMINOSAS: O CASO DO PCC - PRIMEIRO COMANDO DA CAPITAL - Paula dos Santos Bigoli; Eduardo Buzetti Eustachio Bezerro (Universidade do Oeste Paulista, 2014)
This article shows the theory on the largest criminal organization in Brazil: PCC - Primeiro Comando da Capital (First Command of the Capital). This criminal organization was created in House Custody Taubaté by prisoners who promised to fight for their rights against state repression did not care about the situation of prisons: The prison overcrowding situation, inhumane conditions, the cruel punishments and other key factors for that the revolt began. During its 20 year history, the PCC built a criminal empire by eliminating all enemies, creating alliances with other factions and conquering soldiers today are loyal to the law of "party", having the monopoly of crime in the state of São Paulo, where there are few enemies your height.